Transcatheter retrieval of embolized catheter using venovenous loop in a neonate. - YAKUT, KAHRAMAN; Varan, B; Yakut, KAHRAMAN; Harman, A (My University, 2018)
Varan B, Yakut K, Harman A. Transcatheter retrieval of embolized catheter using venovenous loop in a neonate. Turk J Pediatr 2018; 60: 113-115. Umbilical venous catheters are reliable in providing adequate medical care for premature babies however complications include infections, bleeding, thrombosis, catheter occlusion and migration of a piece of catheter to other parts in the body. Here, we present a case with migration of a piece of umbilical venous catheter which has been trapped between hepatic vein and right upper pulmonary vein causing apnea episodes, recurrent respiratory symptoms, need for mechanical ventilation and increase of acute phase reactants. The embolized catheter was retrieved successfully via percutaneous route.
Keywords: Umbilical catheter; Newborn; Complication; Treatment